Błogosławiony Edmund Bojanowski (1814-1871) jako amator archeologii regionalnej. Fragment starożytnictwa w Wielkim Księstwie Poznańskim - Fogel, Jerzy (Folia Praehistorica Posnaniensia, 2018)
Edmund Bojanowski was a son of the impoverished noble Polish family. He spent most of his life in Grabonog near Gostyń (Great Poland). For a short period of time, he studied human sciences, including archaeology, at German universities in Breslau and Berlin. After returning permanently from abroad, Bojanowski has completely devoted himself to a charitable, educational and religious work with people from rural areas. In June 1839 he carried out archaeological excavations of a multicultural prehistoric cemetery in Grabonog. The results of this project were published in a popular weekly magazine „Przyjaciel Ludu” (see appendix I) in 1842. Edmund Bojanowski was a very active member of Kasyno Gostyńskie, which among others, was interested in patriotic antiquities (see appendix II). As the devoted servant of God, Edmund Bojanowski was personally beatified by Pope John Paul II in Warsaw on June 13, 1999.